1995
DOI: 10.1051/rnd:19950401
|View full text |Cite
|
Sign up to set email alerts
|

Essai sur l'adaptation de la fermentation ruminale au monensin

Abstract: Summary ― Adaptation of rumen fermentation to monensin administration. Adaptation of rumen fermentation to monensin feeding has been studied with rumen-fistulated sheep receiving a daily dose of 30 mg of monensin for a period of 21 d followed by a 28 d period during which 60 mg doses were administered. The ration consisted of 300 g of hay and 300 g of concentrates, fed at 9.00 hand 16.00 h. Monensin was placed in the rumen as an aqueous suspension, just prior to the moming feeding. Monensin infusion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…Time had no (P > 0.05) effect on milk fat percentage (Table 2). Figure 1 shows that monensin reduced and sustained a 7 to 9% reduction in CH 4 production (g/d and g/kg of BW) for 6 mo, in agreement with other previous studies (e.g., Davies et al, 1982;Mbanzamihigo et al, 1995Mbanzamihigo et al, , 1996Rogers et al, 1997) that have shown 40-to 240-d CH 4 reductions as long as monensin was fed.…”
Section: Resultssupporting
confidence: 90%
“…Time had no (P > 0.05) effect on milk fat percentage (Table 2). Figure 1 shows that monensin reduced and sustained a 7 to 9% reduction in CH 4 production (g/d and g/kg of BW) for 6 mo, in agreement with other previous studies (e.g., Davies et al, 1982;Mbanzamihigo et al, 1995Mbanzamihigo et al, , 1996Rogers et al, 1997) that have shown 40-to 240-d CH 4 reductions as long as monensin was fed.…”
Section: Resultssupporting
confidence: 90%
“…After short periods of time (up to 30 d) levels of CH 4 production returned to pre‐ionophore supplementation levels, probably due to an ability of the ruminal microflora to adapt to the ionophore (Johnson and Johnson, 1995). The shift in VFA profile (higher percentage of propionate) was maintained for long periods of time (Mbanzamihigo et al, 1995; Richardson et al, 1976; Rogers et al, 1997), indicating that the uncoupling effect of ionophores on CH 4 production and VFA profile is not in agreement with the stoichiometrical relationship of the ruminal fermentation (Wolin, 1960), as long as no other means to eliminate the excess of H + in the rumen is provided (Hino and Asanuma, 2003). On the other hand, several other studies (Davies et al, 1982; Mbanzamihigo et al, 1995, 1996; Rogers et al, 1997) have shown a long‐term (40–240 d) effect of monensin on CH 4 depression with no evidence of microbial adaptation.…”
Section: Effects Of Ionophores On Methane Productionmentioning
confidence: 99%
“…C 2 H 6 (99.99% purity, Air Liquide, Belgium) was infused continuously through the rumen fistula during 6 h at a rate of 10 mL min -1 using a dosimeter (Brooks instruments B.V., G/T 1000, the Netherlands). Total gas expelled through the rumen fistula of each sheep was collected in large PVC columns (17.5 L and 7.5 L) as described by Van Nevel et al (1970) and modified by Mbanzamihigo et al (1995) for monitoring several animals. At the end of the gas collection, total rumen gas produced during 6 h, mixed with C 2 H 6 , was sampled (1 mL) using gas tight syringes.…”
Section: Collection Of Rumen Gasesmentioning
confidence: 99%